Airborne dust pollution emitted by El Hadjar Metallurgical Complex: quantification, characterization, and occupational health hazards - Boutarfa, Fares; Idres, Abdelaziz; Mekti, Zohir; Graine, Radouane; Tiour, Fahem; Dovbash, Nadiia; Benselhoub, Aissa; Bellucci, Stefano (Technology audit and production reserves, 2023)
The iron deposits of Ouenza and Boukhadra represent one of the main sources of iron ore supply for the Algerian steel industry. Being a fundamental wealth available to Algeria, the exploitation of iron ores and its use causes strong negative consequences on the environment, mainly by the expansion of dust, which will be a source of environmental degradation. The metallurgical industry is an integral part of the Algerian economy. Environmental problems that negatively affect the health of people and the environment is air pollution. These issues are relevant to the site and the town of Annaba, where the metallurgical industry is developed. Environmental awareness is characterized by strong environmental sensitization; especially in urban areas with metallurgical pollution sources. The object of this study is taking samples from sites that generate more dust within the steel complex plant. This study aims to characterize steelmaking dust from different sites of the plant in order to identify the mineral phases and their chemical compositions. The various analytical methods used include physico-chemical analysis, X-ray fluorescence (XRF), crystal phases, crystal size, lattice parameters, microdeformations, laser granulometry analysis, X-ray diffraction, microscopy Electronic Scanning and Analysis (EDS) Energy Dispersion Spectroscopy. It was found that the average monthly quantity of dust released by the dust collectors of the Agglomerated Material Preparation (AMP) unit is 108.45 tons. The results obtained from the dust samples analysis of dust samples from the different points of the site differ in their mineral and chemical composition. The research confirmed the presence of iron oxides, silicon, many different mineral phases. The results of dimensional analysis prove that the two samples are different in their sizes ESP1et and ESP2 is coarser than ESP3 and FF3A, these results can lead to long-term occupational illnesses.